Enrolment in workplace multimodal training programmes: The weight of trainee reactions to previous training experiences. (15th February 2022) - Chauvin, Rachel; Yennek, Nora; Laurent, Pauline; Lôrant, Sonia; Fenouillet, Fabien
Abstract: This study investigated the extent to which trainees' perceptions about previous training experiences determine their decision to re‐enrol in future multimodal training programmes. A post‐training reaction instrument adapted to multiple training modalities was developed. The results showed that trainees' perceptions of the training design and utility for professional activities had an impact on their intention to attend training, which in turn affected the decision to re‐enrol in English as a foreign language training programme measured four months later. Trainees less satisfied with their training experience also considered it less useful to reach their goals and were less likely to re‐enrol in future programmes on the same topic. Nevertheless, the level of pre‐training motivation to learn and task self‐efficacy should be monitored, as they can strongly affect perceived training usefulness. Practical and research implications are proposed in the discussion.